Effects of extractants on the yields and selected chemical characteristics of humic acids isolated from tropical saprists peat - Lee, Jia Huey; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2010)
Problem statement: Humic acids are beneficial to soil aggregation, binding of heavy metal, plant growth and many more. However, the isolation of Humic Acids (HA) from its origin is not only time-consuming, but the isolation is also affected by factors such as temperature and the types of extractants and their concentrations. Different concentrations of extractant are said to alter the chemical characteristics of HA. Although this kind of information is important in HA studies, it is lacking for tropical peats. Approach: This study was conducted to investigate the yields and selected chemical element contents of HA isolated from tropical saprists peat as affected by NaOH and KOH with different concentrations. Humic acids were isolated from tropical saprists peat taken from Sarawak, Malaysia. Yields of HA and selected chemical properties were determined using standard procedures. Results: Yields of HA isolated using different concentrations of NaOH and KOH showed significant difference at each level of concentrations. For the chemical characteristics tested, only total acidity showed no significant difference. For TOC and ash, the KOH used exhibited inconsistent results compared to that of NaOH. As for E4/E6 values, the high values obtained suggests that HA in Sarawak peats contain relatively lower molecular weight. Conclusion: For the purpose of studying chemical characteristics, 0.2, 0.3 and 0.4 M of both NaOH and KOH were good enough to be used in isolating HA. This is because the results of study showed that these 3 levels of concentrations yielded HA with more homogenous chemical characteristics. On the other hand, extractants with higher concentrations are preferred when the yield of HA is of concern.